2013
DOI: 10.1117/1.jbo.19.5.051206
|View full text |Cite
|
Sign up to set email alerts
|

In vivoimaging of human adipose-derived stem cells in Alzheimer’s disease animal model

Abstract: Abstract. Stem cell therapy is a promising tool for the treatment of diverse conditions, including neurodegenerative diseases such as Alzheimer's disease (AD). To understand transplanted stem cell biology, in vivo imaging is necessary. Nanomaterial has great potential for in vivo imaging and several noninvasive methods are used, such as magnetic resonance imaging, positron emission tomography, fluorescence imaging (FI) and near-infrared FI. However, each method has limitations for in vivo imaging. To overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…MSCs first accumulate in the lung 24–48 hours after transplantation but can be found later in the liver, kidney, spleen, and other organs, particularly those showing injury [21]. Multimodal MRI nanoparticles with enhanced near-infrared fluorescence have been used recently to perform in-vivo imaging of human adipose-derived stem cells in an Alzheimer’s disease mouse model [22]. Cells administered via tail-vein injection were observed in the tail, body, and brain of Alzheimer’s disease mice up to 10 days after transplantation (with the strongest signal at day 3), but not in the brains of wild-type (WT) controls [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs first accumulate in the lung 24–48 hours after transplantation but can be found later in the liver, kidney, spleen, and other organs, particularly those showing injury [21]. Multimodal MRI nanoparticles with enhanced near-infrared fluorescence have been used recently to perform in-vivo imaging of human adipose-derived stem cells in an Alzheimer’s disease mouse model [22]. Cells administered via tail-vein injection were observed in the tail, body, and brain of Alzheimer’s disease mice up to 10 days after transplantation (with the strongest signal at day 3), but not in the brains of wild-type (WT) controls [22].…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal MRI nanoparticles with enhanced near-infrared fluorescence have been used recently to perform in-vivo imaging of human adipose-derived stem cells in an Alzheimer’s disease mouse model [22]. Cells administered via tail-vein injection were observed in the tail, body, and brain of Alzheimer’s disease mice up to 10 days after transplantation (with the strongest signal at day 3), but not in the brains of wild-type (WT) controls [22]. Post-mortem examination of organs revealed weak fluorescent signals in WT brain tissue, suggesting that some cells are able to cross the blood–brain barrier (BBB) in young animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIR imaging offers new opportunities as a sensitive and noninvasive detection technique for diagnostics that allows deeper penetration into tissues with minimum background interference. 18,19 The successful clinical application of MSC-based tumor therapies needs noninvasive imaging approaches for monitoring tumor progression and treatment outcomes in real time.…”
Section: Introductionmentioning
confidence: 99%
“…The transplantation of ADSCs allowed them to differentiate into neuron-like and astrocyte-like cells around the hematoma, accompanied with up-regulation of vascular endothelial growth factor expression and improvement of neural function, suggesting that ADSCs benefit neural differentiation and induce functional improvement in the rat [47]. When human ADSCs were intravenously injected into an AD mouse models, these cells could be found in the brain up to 12 days after their injection [48]. One report suggested that, when transplanted into the brain, adipose-derived MSCs (AMSCs) improved Ach levels as well as cognitive and locomotor functions in aged mice, and modulated microglia activation [29,49].…”
Section: Stem Cell Treatment For Admentioning
confidence: 99%